Trichoderma-fortified compost extracts for the control of Chaonephora wet rot in okra production. - Siddiqui, Yasmeen; Meon, Sariah; Ismail, Mohd Razi; Ali, Asgar (Elsevier Ltd., 2008)
The potential of water extracts produced from rice straw (RST) and empty fruit bunch of oil palm (EFB) composts fortified with Trichoderma harzianum for the control of Choanephora wet rot of okra caused by Choanephora cucurbitarum was studied under field conditions. Disease severity was lowest in plants treated with Trichoderma-fortified RST extracts (9.56%) with a disease index of 1, mancozeb (Dithane M-45® (2 g l−1 of water), Trichoderma-fortified EFB compost extracts, extracts of RST and EFB, and an aqueous suspension of T. harzianum recorded disease severity values of 10.25%, 19.38%, 37.56%, 53.71% and 56.36%, with a disease index of 1, 1, 2, 3 and 3, respectively. There was a reduction of 85.04% in Choanephora wet rot severity on okra treated with Trichoderma-fortified RST extracts during 12 weeks of assessment in the field, which was comparable to the conventional fungicide Dithane M-45®, suggesting that application of extracts produced from well-matured compost fortified with biocontrol agents could be an alternative control strategy.